Avian molecular evolution and systematics - Mindell, David P. (Academic Press, 1997)
The use of DNA and other biological macromolecules has revolutionized systematic studies of evolutionary history. Methods that use sequences of nucleotides and amino acids are now routinely used as data for addressing evolutionary questions that, although not new questions, have defied description and analysis. The world-renowned contributors use these new methods to unravel particular aspects of the evolutionary history of birds. Avian Molecular Evolution and Systematics presents an overview of the theory and application of molecular systematics, focusing on the phylogeny and evolutionary biology of birds. New, developing areas in the phylogeny of birds at multiple taxonomic areas are covered, as well as methods of analysis for molecular data, evolutionary genetics within and between bird populations, and the application of molecular-based phylogenies to broader questions of evolution. Key Features * Contains authoritative contributions from leading researchers * Discusses the utility of different molecular markers for questions of avian evolution, involving populations and higher-level taxa * Applies molecular-based phylogenies of birds and molecular population genetics data to broad questions of organismal and molecular evolution. * Compares and contrasts molecular and morphological data sets.